Narrating risk: the financial thriller film during the U.S. recession. Issue 3 (16th April 2017) - Clavin, Keith
ABSTRACT: The following article examines contemporary cinema's narrative responses to the 2007 credit crisis and subsequent recession in the United States. The analysis focuses upon Margin Call (2011) and Cosmopolis (2012), two films that draw from the genre commonly referred to as 'the thriller'. Both films are fictional and exhibit the interplay between systemic risk, the revision of historical conventions of the thriller, and financial crisis. Specifically, the narratives build their central dramatic tensions around representations of the persistent challenge to locate, quarantine, and coordinate networked responses against systemic risk, a challenge which comes to symbolise the fundamental struggle of a global financial culture. Within these films, systemic risk is represented through a new set of semiotic codes involving technology and mathematics, which work to join near-automated financial industries of late-stage capitalism with an appearance of human relevancy. When positioned against the rhetorical specifics of U.S. congressional hearings and news media reports about the crisis, a dynamic pattern about 'thrills' and risk begins to emerge wherein the films' representational fields and the adopted structures of the allegedly nonfictional, expert language form a reciprocal relation.